Nordic pole walking improves walking capacity in patients with intermittent claudication: a randomized controlled trial. Issue 13 (18th June 2016) - Bulińska, Katarzyna; Kropielnicka, Katarzyna; Jasiński, Tomasz; Wojcieszczyk-Latos, Joanna; Pilch, Urszula; Dąbrowska, Grażyna; Skórkowska-Telichowska, Katarzyna; Kałka, Dariusz; Zywar, Katarzyna; Paszkowski, Rafał; Woźniewski, Marek; Szuba, Andrzej; et al.
Abstract: Purpose : The aim of the study was to compare the efficacy of Nordic pole walking (NPW) training with traditional treadmill training (TT) on a claudication (CD) and maximum walking distance (MWD) in patients with peripheral arterial disease (PAD). Method : Patients with intermittent claudication (IC) ( n  = 70; age=68.27) in the Fontaine class II were randomized into a two three-month rehabilitation programs performed three times per week. TT were finished by 31 patients, NPW by 21. Walking capacity was measured by an exercise treadmill test (ETT) with the Gardner–Skinner protocol (before and after the program) and six minute walk test (6MWT) (before, during and after the program). Results : In an ETT both groups reached significant increase in CD and MWD ( p  ≤ 0.005). In 6MWT NPW group reached significant increase in both CD ( p  = 0.001) and MWD ( p  = 0.001), whereas the TT group only in MWD ( p  = 0.001). Conclusions : NPW has been shown to be as effective as the standard TT and is much less expensive. It should be the preferred method of exercise for PAD patients with IC. Implications for Rehabilitation: Nordic walking training is a valuable form of rehabilitation for peripheral arterial disease (PAD) patients with intermittent claudication (IC). Nordic walking has been shown to be as efficient as traditional treadmill training. It is however more cost-effective method of rehabilitation in PAD patients.